Functional genomics and proteomics: recent developments of the search in poligenic diseases and ethical considerations. - Bompiani, Adriano (Medicina e Morale, 2003)
The author completes a review of the technologies defined functional genomics and proteomics and illustrates their application for the better knowledge of the complex, more widespread poligenic-multifactorial diseases (more of the 1% of the adult population), that cause elevated morbidity and mortality. The possibilities offered by the DNA-microarray in the analysis of the nucleotide polymorfisms - which are correlated to potentialities offered by informatics supports - characterise the post-DNA sequencing genetics and allow the analysis of gene expression profiles. The development of the modern techniques of protein investigation allows, in turn, to recognise the proteins that are correlated to diseases through their modified levels of expression compared with those deriving from healthy subjects. These beginning researches offer certainly positive judgements if they are evaluated under the scientific knowledge profile, but they are not deprived of risks and reserves under the ethical profile. The author examines their different aspects that concern both the single person and the community. In well circumscribed cases, if they can stimulate favourable behaviours to the prevention of late-onset diseases, forms of sociobiologistic reductionism, dangers of discrimination and, above all, - in prenatal age - wide expressions of that eugenism that characterises negatively the contemporary society are to fear.